Familial treacher collins syndrome- from an obstetrician’s view - Saini, Chesta; Rajurkar, Kishore; Saini, Rizul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
A number of genetic syndromes have been identified and can be diagnosed antenatally using ultrasonography signifying the importance of antenatal care. We report a rare case of familial treacher collins syndrome diagnosed postnatally that shows difficulties faced by an obstetrician to safely manage such cases.